The interplay between leg kick efficiency and pushing phase acceleration in determining the "turning speed" in front crawl swimming - Zamparo, P.; Vicentini, M.; Zorzi, E.; Scattolini, A.; Rigamonti, A.; Bonifazi, M. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Several factors are expected to determine the swimming speed after a turn (before resuming the arm stroke at the surface level). We focused our attention on the contribution of the acceleration during the pushing phase and of the efficiency of the underwater undulatory movement in determining the time taken to cover the first 5 m after the turn in a simulated 100 m race conducted in a 50 m swimming pool. METHODS: Thirteen subjects participated to the study: 5 (4M/1F) elite swimmers of the Italian National Swimming Team and 7 (3M/4F) swimmers competing at local/national level. They were asked to swim the 100 m distance as fast as possible; during this simulated race we recorded their speed in the first 5 m after the turn (v50-55). In a separate series of experiments, the average acceleration during the push (apush, an index of the force exerted during the push) was calculated based on kinematic data collected by means of an underwater video camera; in these experiments the subjects were asked not to kick after the pushing phase, just to glide. In a further series of experiments the subjects were asked to swim underwater by using the dolphin kick while passing in front of an underwater video camera in order to calculate the Froude efficiency of the leg kick ( F) as proposed by Zamparo et al. (2002). RESULTS: Average speed in the first 5 m after the turn (v50-55) was 3.09 ± 0.78 m/s (range: 1.98-4.63); average acceleration during the push (apush) was 2.80 ± 0.69 m . s-2 (range: 1.76-3.85); Froude efficiency of the dolphin kick ( F) was 0.67 ± 0.02 (range: 0.65-0.70). A good relationship was observed between v50-55 and F (R = 0.704, P = 0.011) as well as between v50-55 and apush (R = 0.680, P = 0.015). A multiple regression analysis indicates that these two factors, explain 73% of the variability of v50-55 after a turn (P = 0.035). DISCUSSION: As hypothesized apush and F are well related to the "turning speed" (v50-55) in a simulated 100 m race. Hence both "factors" should be taken into account for a proper training of this "phase" of a swimming race. REFERENCES: 1. Zamparo P, Pendergast DR, Termin B, Minetti AM (2002). How fins affect the economy and efficiency of human swimming. J Exp Biol 205: 2665-2676.